Conjugated Polymers for Microwave Applications: Untethered Sensing Platforms and Multifunctional Devices. Issue 33 (15th July 2022) - Tan, Siew Ting Melissa; Giovannitti, Alexander; Marks, Adam; Moser, Maximilian; Quill, Tyler J.; McCulloch, Iain; Salleo, Alberto; Bonacchini, Giorgio E.
Abstract: In the past two decades, organic electronic materials have enabled and accelerated a large and diverse set of technologies, from energy‐harvesting devices and electromechanical actuators, to flexible and printed (opto)electronic circuitry. Among organic (semi)conductors, organic mixed ion–electronic conductors (OMIECs) are now at the center of renewed interest in organic electronics, as they are key drivers of recent developments in the fields of bioelectronics, energy storage, and neuromorphic computing. However, due to the relatively slow switching dynamics of organic electronics, their application in microwave technology, until recently, has been overlooked. Nonetheless, other unique properties of OMIECs, such as their substantial electrochemical tunability, charge‐modulation range, and processability, make this field of use ripe with opportunities. In this work, the use of a series of solution‐processed intrinsic OMIECs is demonstrated to actively tune the properties of metamaterial‐inspired microwave devices, including an untethered bioelectrochemical sensing platform that requires no external power, and a tunable resonating structure with independent amplitude‐ and frequency‐modulation. These devices showcase the considerable potential of OMIEC‐based metadevices in autonomous bioelectronics and reconfigurable microwave optics. Abstract : The active reconfigurability of different microwave resonating structures is achieved through an emerging family of high‐performance organic mixed‐conductors, characterized by superior charge‐transport properties and redox‐tunability. This novel class of microwave devices displays optimal modulation performances, as well as the potential for unique functionalities in the contexts of autonomous bioelectronics and of reconfigurable microwave optics.